Oncogenic transformation of mammalian cells in vitro with split doses of x-rays. - Miller, R C (1979)
An established line of mouse fibroblasts, C3H/10T1/2 cells, was used for the assessment in vitro of oncogenic transformations caused by single and split doses of x-rays. The shape of the dose-response relationship was determined over the range from 0.1 to 10 Gy. It was found that splitting the x-ray dose into two equal fractions, separated by 5 hr, led to a reduction in transformation frequency at doses above 1.5-2 Gy but to an enhancement of transformation at lower doses. The observations reported cast doubt on the assessment of human cancer risk at lo dose levels by a linear extrapolation from available high-dose data from the Japanese atomic bomb survivors or from persons exposed for medical purposes.